Supercritical carbon dioxide extraction of castor oil seed - Danlami, Jibrin Mohammed (2015)
This study investigates the extraction of castor oil using supercritical carbon dioxide (SC-CO2). The response surface methodology (RSM) was employed to show explicitly the influence of the process parameters such as temperature, pressure and CO2 flow rate on the oil yield using the Box-Behnken design. The linear terms of pressure, CO2 flow rate and temperature, and the quadratic terms of temperature, pressure and CO2 flow rate had a significant effect on the oil yield. The maximum oil yield obtained from the mathematical model was predicted to be 9.29% under the conditions of temperature at 63.7 °C and pressure of 29.9 MPa with CO2 flow rate of 4.15 mL/min. Comparing the oil yield with the conventional soxhlet extraction, yields of 59.8%, 52.3% and 49.9% were obtained using ethanol, n-hexane and petroleum ether as solvents for optimized average particle sizes and extraction times of 1.30 mm and 2.88 h, 1.26 mm and 2.65 h and 1.25 mm and 2.55 h, respectively. In addition, the solubility of castor oil was measured at temperatures ranging from 313 to 335 K, and pressures 20 to 36 MPa, respectively. The measured solubilities ranged from 1.00 × 10-3 to 4.88 × 10-3 g of oil/g of CO2. The measurements confirmed that temperature and pressure have direct effects on solubilityenhancement factors. Five semi-empirical models were tested for correlating the experimental data from SC-CO2 extraction: the Chrastil, Del Valle Aguilera (VA), Bartle, Kumar and Johnston (KJ) and Mendez-Santiago and Teja (MST) models. The solubilities from these models had the following average absolute relative deviations (AARD%) from experimental data: 0.05% (Chrastil), 0.30% (VA), 0.38% (Bartle), 5.98 % (KJ) and 28.5% (MST). Thus, the Chrastil, VA and Bartle models correlated to the castor oil solubility data with the lowest AARD%. The physico-chemical properties of the seed oil extracted using the SC-CO2 and soxhlet methods were determined. Palmitic, stearic, oleic, linoleic, linolenic and ricinoleic acids were identified by gas chromatography-mass spectrometry (GC-MS) analysis after the formation of fatty acid methyl ester (FAME). For oxidation stability, castor oils derived from these extraction methods were heated in an oven at 70 °C for 0–12 weeks. The quality and oxidative stability of oil recovered by SC-CO2 were generally found to be better than that recovered by the soxhlet method. In addition, the parameters considered in this study, namely peroxide value, refractive index, pH, conductivity, acid value and free fatty acid offer an appropriate tool for evaluating the quality of castor oil during storage as well as its oxidative stability; the study also sheds light on the different responses of castor oil during storage.